2004
DOI: 10.1115/1.1677450
|View full text |Cite
|
Sign up to set email alerts
|

Fraction Solid Measurements on Solidifying Melt

Abstract: A new indirect method to measure fraction solid in molten metals is presented. The method is based on the phenomena that when a metal sample (solid or liquid) rotates in a magnetic field (or the magnetic field rotates around a stationary sample), circulating eddy currents are induced in the sample, which generate an opposing torque related to amount of solid phase in a solidifying melt between the liquidus and solidus temperatures. This new technique is applied for measuring fraction solid on commercial A319 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…However, the linear rule is preferred for its simplicity. The recent work of Bakhtiyarov et al [13] demonstrated that for Al alloy the results from the linear relation relationship and from Scheil model do not differ significantly.…”
Section: Simulation Strategymentioning
confidence: 89%
“…However, the linear rule is preferred for its simplicity. The recent work of Bakhtiyarov et al [13] demonstrated that for Al alloy the results from the linear relation relationship and from Scheil model do not differ significantly.…”
Section: Simulation Strategymentioning
confidence: 89%
“…This can be done by measuring properties such as electrical potential difference or uniaxial flow stress and mathematically relating the obtained values to the fraction solid. [9] Recently, Bakhtiyarov et al [10] presented a method where the opposing torque generated in the sample by a surrounding rotating magnetic field is related to the amount of solid phase in a solidifying melt. At the present time, the literature provides very few details about these indirect methods, which will not be considered further here.…”
Section: Comparison Of Different Methods To Determine Solidificatmentioning
confidence: 99%
“…The calculation of the solid fraction was performed using the Newtonian assumption. [10][11][12][13][14] The result is stated in Fig. 15, which reveals a loss of monotonicity at the isofraction contours at a distance of 15 mm from the cooling plate and time longer than 100 s. There is an extended period of time for f s (0?2 to areas up to 15 mm to the cooling plate.…”
Section: Resultsmentioning
confidence: 83%